Molecular detection of some virulence gene in Proteus mirabilis isolated from chicken and human - Aamer Y. Alchalaby; Balsam Y. Rasheed; Ammar M. Al-AAlim (Iraqi Journal of Veterinary Sciences, 2025)
The goal of this significant study is to isolate Proteus spp from both human and broiler sources and to compare the presence of the most significant genes responsible for virulence factors like zapA, rsp A, and ure C. This research, conducted from September 2023 to February 2024, collected twenty-five samples from the internal organs of broilers (heart, lung, liver, air sac, meat) and twenty-five samples from urinary tract infections in humans. The standard bacteriological method was used for bacterial identification, and PCR confirmed the Proteus spp isolates. Further sequencing and phylogenetic analysis of zap A were conducted. The study revealed 23 isolates of P. mirabilis from a total of 25 broiler samples, at a rate of 92%, while the isolation rate in humans was 88%, with 22 isolates from 25 urine samples. Molecular examination showed that all zap A, rsbA and ure C genes were found in both human and poultry isolates. The phylogenetic analysis shows that all Proteus isolates aggregate in one clade. In conclusion, our findings underscore the potential danger of virulence genes in poultry, a human staple food. This highlights the crucial need for caution in meat processing and the use of effective methods to prevent infection and sterilize meat before human consumption.